A Identification Test Of Borax And Formaline Content In Food Sold At Laguboti Market - Yanti, Fitri; Hepni; Wydia Simamora (International Journal of Health Engineering and Technology, 2023)
Food is one of the human needs in everyday life. As a basic need, these foods must contain nutrients to be able to fulfill this function and be safe. Preservatives and dyes seem to be inseparable from various types of processed food and beverages. The purpose of this study was to determine the presence or absence of borax and formalin in food sold at the Laguboti Market. Based on Permenkes Number 033 of 2012 concerning food additives, borax is not allowed in food. If borax and formalin are consumed by humans, it will have a negative impact on the body. This study used a descriptive method, namely the scientific method and the simple method and was carried out in July at the Chemistry Laboratory of STIKes Arjuna Laguboti with a total sample of 14 food samples purchased from different food vendors at the Laguboti Market. Based on the results of a qualitative analysis on borax using the scientific method and the simple method obtained from 3 meatball samples and 3 rice cake samples, none of the meatballs contained borax. In formalin Using the scientific method and simple methods obtained from 5 samples of tofu and 3 samples of wet noodles containing formalin.